The design and evaluation of the antimicrobial activity of a novel conjugated penta-ultrashort antimicrobial peptide in combination with conventional antibiotics against sensitive and resistant strains of S. aureus and E. coli. - Rula Darwish; Ammar Almaaytah; Ali Salama (Research in Pharmaceutical Sciences, 2022)
Background and purpose: Antimicrobial resistance still constitutes a major health concern to the global human population. The development of new classes of antimicrobial agents is urgently needed to thwart the continuous emergence of highly resistant microbial pathogens. Experimental approach: In this study, we have rationally designed a novel conjugated ultrashort antimicrobial peptide. The peptide named naprolyginine was challenged against representative strains of wild-type and multidrug-resistant bacteria individually or in combination with individual antibiotics by employing standard antimicrobial and checkerboard assays. Findings / Results: Our results displayed that the peptide exhibits potent synergistic antimicrobial activity against resistant strains of gram-positive and gram-negative bacteria when combined with individual antibiotics. Additionally, the peptide was evaluated for its hemolytic activity against human red blood cells and displayed negligible toxicity. Conclusion and implications: Naprolyginine could prove to be a promising candidate for antimicrobial drug development.